Amylase-Functionalized mesoporous silica thin films as robust biocatalyst platforms - Bellino, Martin Gonzalo (2010)
A robust biocatalyst was produced by immobilization of R-amylase into mesoporous silica thin films with local order pore structure and 11 nm pore diameter, supported on glass stripes. The activity of this novel catalyst was evaluated for direct starch degradation. The catalyst films show excellent activity, and enhanced stability with respect to free enzyme at extreme conditions of pH and temperature. In addition, they can be easily separated from the reaction media and reused several times.